Improvement of graphene oxide characteristics depending on base washing - Kabel, Kh.I.; Farag, Ah.A.; Elnaggar, E.M.; Al-Gamala, A.G. (Сверхтвердые материалы, 2015)
Graphene oxide (GO) has been synthesized using Hummer’s method. This oxidation process decorates the graphene sheets by different types of functional groups, yet the harsh oxidation condition leads to introduce many of carbonaceous fragments, which decreasing GO efficiency in many faces, touched its applications. The synthesized GO has been washed by 10 M NaOH to produce (GOn). Thereafter quality enhancement of GO has been studied by several analyses; the introduced hydroxyl and carboxyl groups into few-layer graphene (FLG) surface have been determined by Fourier transform infrared spectra (FTIR). Raman spectroscopy analysis identified the defect degree and the transition of graphite from a crystalline to an amorphous structure and vice versa. The interlayer spacings of FLG and GOn were investigated by Xray diffraction (XRD) and the thermal stability of as-received and modified materials were examined by thermal gravimetric analysis (TGA). The morphological structure was characterized by scanning electron microscopy (SEM) and high resolution transmission electron microscopy (HRTEM). The various investigations confirmed that the properties of GO were improved by neutralization impact, which may pave the way to new developments in the GO-based applications.